Chapter Nemesi tecnologica, pace distopica: l'espropriazione della pace - Belli, Carlo (Studi e saggi, 2022)
Umberto Gori has often focused on the subject of peace, seen as the primary objective of Political Science, analysing the challenges that peacebuilding processes have to face in an international context undergoing profound change, and with aspects that could be described as dystopic. We will explore these dynamics by drawing inspiration from the way in which Ivan Illich dealt with the theme of the forced medicalisation of society, a theme that presents many points of contact with the intention of imposing a distorted version of the concept of peace, where a model of peaceful coexistence is proposed, which does not arise from the development of stable harmonious relations between mutually free and independent subjects, but from an absence of conflict produced by dehumanising forms of social conditioning.